Safety of multicomponent meningococcal group B vaccine (4CMenB) in routine infant immunisation in the UK: a prospective surveillance study. (June 2018) - Bryan, Philip; Seabroke, Suzie; Wong, Jenny; Donegan, Katherine; Webb, Elizabeth; Goldsmith, Charlotte; Vipond, Caroline; Feavers, Ian
Summary: Background: Safety data for the multicomponent meningococcal group B vaccine (4CMenB) has so far been limited to experience from clinical trials and isolated local outbreaks. Since the UK is the first country to implement a nationwide routine immunisation programme with 4CMenB (at age 8 weeks, 16 weeks, and then 1 year), we aimed to assess the safety of 4CMenB in this setting. Methods: In this prospective surveillance study, we assessed suspected adverse reactions of 4CMenB in children up to age 18 months reported in the UK Yellow Card Scheme and primary care records extracted from the Clinical Practice Research Datalink (CPRD). We proactively assessed reports of fever, local reactions, Kawasaki disease, seizures, and sudden death, and compared the number of spontaneous reports with the expected number of events based on background incidence and the number of children vaccinated. We also identified any unexpected adverse reactions and estimated compliance with subsequent doses of routine vaccinations. Findings: From Sept 1, 2015, to May 31, 2017, approximately 1·29 million children aged 2–18 months received about a combined 3 million doses of 4CMenB. 902 reports of suspected adverse reactions were received through the UK Yellow Card Scheme, of which 366 (41%) were related to local reactions and 364 (40%) related to fever. The only unexpected finding was that 160 reports of local reactions described a persistent nodule at the site of injection, usually without other local symptoms. There were 55 (6%) reports of seizures, with an age-adjusted observed-to-expected ratio of 0·13 (95% CI 0·10–0·17). Ecological analyses found similar rates of seizures within 7 days of routine immunisation in the periods before and after 4CMenB introduction, with incidence rate ratios of 1·30 (95% CI 0·56–3·00) at age 2 months, 1·53 (0·49–4·74) at age 4 months, and 1·26 (0·69–2·32) at age 12 months. Of the 902 reports, three (<1%) were of Kawasaki disease (observed-to-expected ratio 1·40, 95% CI 0·29–4·08) and three (<1%) of sudden infant death syndrome within 3 days of vaccination in children aged 2–4 months (0·44, 0·12–1·14). Analysis of routine immunisations recorded in CPRD found that 11 602 (95·1%) of 12 199 children had received the second dose of 4CMenB by 26 weeks of age, 1793 (84·7%) of 2117 had received the third dose by 62 weeks of age, and 4CMenB introduction had not reduced compliance with doses of other routine vaccinations. Interpretation: We found no significant safety concerns after widespread use of 4CMenB in UK infants, and the vaccine appears to have been well accepted by parents. However, it is important to continue monitoring the safety and long-term effect of the immunisation programme in the UK to further characterise the reported suspected adverse reactions. Funding: None.